Idioms in the Literary Works of Desa Muck - Markežič, Tjaša (Trideset let literarne nagrade večernica, 2026)
This article explores the use of idioms in five works of young adult literature by Desa Muck that were nominated for or received the Večernica Award. The analysis reveals that the identified idioms are associated with a range of stylistic markers and are highly diverse in terms of their origins. Moreover, they play an important role in creating humour and irony, characterising literary figures, and enhancing the emotional expressiveness of the narratives.